Active learning to develop disciplinary competencies related to automatic control in engineering curricula using low cost do-it-yourself didactic stations - Navarro-Durán, David; Félix-Herrán, Luis C.; Membrillo-Hernández, Jorge; Craig, Kevin C.; Ramírez-Cadena, Miguel J.; Ramírez-Mendoza, Ricardo A. (Frontiers in Education, 2023)
Usually, in automatic control courses, the process of designing and testing a control system includes applying physical laws to model the system, working with virtual models, building one or various prototypes, and testing the control algorithms. However, in the industry, the approach has to be more pragmatic because the design and implementation time has to be shorter, and the success of the solution must be ensured. Faced with this problem, a black-box model from which data is generated, turns into a convenient starting point to design and implement the automation, and this approach is addressed in this research. The herein proposal is the design and implementation of didactic stations, and their application in undergraduate automatic control courses. In the context of active learning, by using the stations to identify the model’s dynamics, and subsequently, design and implement an automatic system, students reinforce the theory and receive another stimulus for the development of competencies in automatic control. The didactic stations emulate those cases in the industry where the hardware is already working and it is necessary to automate or improve some process following a practical approach. During the first phase, students guided by professors, designed and implemented four electromechanical prototypes; and the second phase was using the prototypes in the curricular courses Control Engineering and Computerized Control for the purpose of implementing and evaluating controllers. The research included a control group and an experimental group. The group using the stations had a higher final course average grade than the control group. The findings encourage the application of this type of approach to complement the teaching of automatic control, which could positively impact on the professional performance of future control engineers.